Weight control interventions improve therapeutic efficacy of dacarbazine in melanoma by reversing obesity-induced drug resistance - Malvi, Parmanand (Cancer Metab, 2016)
BACKGROUND: Obesity-related cellular, metabolic, and molecular alterations have been shown to increase cancer risk and tumor progression and are associated with poorer therapeutic outcome in cancer patients. However, the impact of obesity and weight-control interventions on the therapeutic response in melanoma is poorly understood. METHODS: High fat diet (HFD)-induced obese mouse model was used in this study to evaluate the outcome of dacarbazine (DTIC) therapy in melanoma. We employed LC-MS/MS to determine the quantity of the drug in tumor, and in various tissues. Unique in vitro approach was used to complement in vivo findings by culturing melanoma cells in either conditioned medium (CM) obtained from differentiated adipocytes or in serum collected from experimental mice. RESULTS: We report that diet-induced obesity impairs the outcome of DTIC therapy and reduces overall survival in tumor-bearing mice. We provide evidence that obesity restricts the accessibility of DTIC to tumor tissue. Critically, upon curtailing adiposity, accumulation and efficacy of DTIC is significantly improved. Moreover, using appropriate in vitro approaches, we show that melanoma cells exhibit a drug-resistant phenotype when cultured in serum collected from diet-induced obese mice or in CM collected from 3T3-L1 adipocytes. The impaired therapeutic response to DTIC in obese state is mediated by fatty acid synthase (FASN), caveolin-1 (Cav-1), and P-glycoprotein (P-gp). The response to DTIC and overall survival were improved upon employing weight control interventions in the tumor-bearing HFD-fed (obese) mice. CONCLUSIONS: This study indicates that obesity not only supports rapid melanoma progression but also impairs the outcome of chemotherapy, which can be improved upon employing weight control interventions. From clinically relevant point of view, our study exemplifies the importance of lifestyle interventions in the treatment of obesity-promoted cancers. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40170-016-0162-8) contains supplementary material, which is available to authorized users.